1995
DOI: 10.1051/parasite/1995022173
|View full text |Cite
|
Sign up to set email alerts
|

A new zoonosis of the cerebrospinal fluid of man probably caused byMeningonema peruzzii, a filaria of the central nervous system of Cercopithecidae

Abstract: Summary :A femal e fourth stage larva of Meningonema, probably of M. peruzzii Orihel et Esslinger, 1973, was recovered in Cameroon, from the cerebtospinal fluid of a pati ent harbouring Loa loa, but without any neurological signs. This observation is the first human case of Meningonema (Filatioidea Splendidofilatiinae) which usually parasitizes the central nervous system of African Cercopithecinae. However, as i ndi cated by Orihel and Esslinger, it seems probabl e that the perstans-like microfilariae describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…These findings are in agreement with other studies that showed that M. peruzzii could be found in blood or CSF or in both [1, 15, 17].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are in agreement with other studies that showed that M. peruzzii could be found in blood or CSF or in both [1, 15, 17].…”
Section: Discussionsupporting
confidence: 94%
“…This indicated that the lesions were possibly due to bacterial infection of traumatic injuries, resulting possibly from fights within the troops. These findings are in agreement with other studies that showed that M. peruzzii could be found in blood or CSF or in both [1,15,17].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These microfilariae were likely responsible for the generalized immune response as well as for the involvement of the central nervous system. Microfilariae that cross the blood-brain barrier and cause neurologic symptoms in humans or animals have been previously described for other species such as Meningonema peruzzi and D. immitis ( 12 , 13 ). In the case presented here, infection was most likely acquired in India or Sri Lanka, 2 regions where D. repens is endemic ( 7 , 8 , 14 , 15 ).…”
Section: Resultsmentioning
confidence: 92%
“…15 The only two well-documented cases attributed to M. perstans have subsequently been shown to be due to Meningonema peruzzii, a filaria of monkeys (Cercopithecidae), a parasite of whose fourth-stage larva has also been found in the CSF of humans. [16][17][18] Another fourth argument is based on pathologic findings that have shown that in all autopsies of encephalopathic cases involving L. loa, the cerebral tissue was diffusely invaded by mf causing microinfarcts and microthromboses. [19][20][21][22] In contrast, neurologic manifestations attributed to lymphatic filariasis have been recorded on only eight occasions, [23][24][25][26][27][28][29][30] and the cerebral lesions involved were generally limited to local granulomata.…”
Section: Discussionmentioning
confidence: 99%